Sociocultural Issues as Barriers to HIV-Infected Orphan Care in Southern Africa - Langsam Seth; Lehmann Corinne; M. Vaughn Lisa; Kissling Alexandra (Journal of Clinical Research In HIV AIDS And Prevention, 2014)
As advances in treatment and prevention are starting to decrease the magnitude of the Acquired Immunodeficiency Syndrome (AIDS) epidemic in Sub-Saharan Africa, the number of orphans and children surviving Human Immunodeficiency Virus (HIV) infection is growing. To date, little research has been conducted in the care of HIV-infected children in orphanages in Sub-Saharan Africa. In this qualitative study, managing personnel in 10 programs caring for HIV-infected children were interviewed to ascertain perceived barriers to care of these children. While all programs commented on medical infrastructure barriers, respondents felt sociocultural issues were more pressing. After analysis of transcribed interviews, three major themes of poverty, denial/stigma, and cultural differences with outsiders emerged. These findings have implications for international programs that both serve and seek to serve the needs of HIV-infected children and orphans in Africa. Outside funding organizations will need to address local poverty, stigma, and African “ownership” of HIV-positive orphans to ultimately ensure the best care of these vulnerable children.
Keywords: Orphans and vulnerable children